Benefits of a non-traditional science communication and internship experience based on research from the National Science Foundation Research Traineeship at a Research Intensive University - Sukanya Dasgupta; Tayler Schillerberg; Haven Cashwell; Chandana Mitra; Karen S. McNeal (PLoS ONE, 2025)
Effective science communication and stakeholder engagement are crucial skills for climate scientists, yet formal training in these areas remains limited in graduate education. The National Science Foundation Research Traineeship (NRT) at Auburn University (AU) addresses this gap through an innovative program combining science communication training with co-production approaches to enhance climate resiliency of built, natural, and social systems within the Southeastern United States (US). This paper evaluates the effectiveness of two novel graduate-level courses: one focused on science communication for non-technical audiences and another combining co-production methods with practical internship experience. Our research employed a mixed-methods approach, including a comprehensive analysis of course catalogs from 146 research-intensive universities and qualitative assessment of student experiences through surveys and descriptive exemplars. Analysis revealed that AU’s NRT program is unique among peer institutions in offering both specialized science communication training and co-production internship opportunities to graduate students across departments. Survey data from 11 program participants and detailed case studies of three program graduates demonstrated significant professional development benefits. Key outcomes included enhanced stakeholder engagement capabilities, improved science communication skills, and better preparation for both academic and non-academic careers. These findings suggest that integrating structured science communication training with hands-on co-production experience provides valuable preparation for climate scientists. The success of AU’s program model indicates that similar curriculum structures could benefit graduate programs nationwide, particularly in preparing students to effectively communicate complex scientific concepts to diverse audiences and engage with stakeholders in climate resilience efforts.